2019
DOI: 10.1108/ijius-07-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Optimal path planning of mobile robot using the hybrid cuckoo–bat algorithm in assorted environment

Abstract: Purpose The purpose of this paper is to obtain an optimal mobile robot path planning by the hybrid algorithm, which is developed by two nature inspired meta-heuristic algorithms, namely, cuckoo-search and bat algorithm (BA) in an unknown or partially known environment. The cuckoo-search algorithm is based on the parasitic behavior of the cuckoo, and the BA is based on the echolocation behavior of the bats. Design/methodology/approach The developed algorithm starts by sensing the obstacles in the environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In robotics, several problems have been solved successfully by BA include tracking system [ 62 , 63 ], mobile robot [ 118 , 217 ], path planning and UAV path planning [ 178 , 182 , 305 , 342 ], and robotics [ 166 , 232 , 250 , 283 , 289 ]. These applications are demonstrated in Fig.…”
Section: Applications Of Bat-inspired Algorithmmentioning
confidence: 99%
“…In robotics, several problems have been solved successfully by BA include tracking system [ 62 , 63 ], mobile robot [ 118 , 217 ], path planning and UAV path planning [ 178 , 182 , 305 , 342 ], and robotics [ 166 , 232 , 250 , 283 , 289 ]. These applications are demonstrated in Fig.…”
Section: Applications Of Bat-inspired Algorithmmentioning
confidence: 99%
“…A hybrid mobile robot path planning algorithm was proposed in [3] that combines two nature-inspired meta-heuristics, based on cuckoo and bat behaviors, i.e., the parasitic behavior of cuckoos and the echolocation behavior of bats. The algorithm was further improved and tested using a real robot in [21]. The test results indicated that, although accuracy has been improved, the two algorithms require tuning parameters that might affect their performance in a complex environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CSA is built on three basic rules: 1 each cuckoo lays one egg at a time in a randomly selected nest; 2 the best nests with quality eggs will be passed on to future generations; and 3 the number of nests in CSA is fixed and the eggs left will be found with a probability between 0 and 1 by the host bird. If the host bird finds the cuckoo egg, it will either get rid of the egg or leave the existing nest to establish a new nest Gunji et al, 2019) CSA uses a combination of local and global random walk. p a indicates the discovery rate of alien nests, which is shown in the following formula that controls this combination.…”
Section: Cuckoo Search Algorithmmentioning
confidence: 99%